1978
DOI: 10.1007/bf01393576
|View full text |Cite
|
Sign up to set email alerts
|

Metal benz oylpivaloylmethanates, part I. Free ligands and copper(II) chelates

Abstract: Syntheses and properties of para-substituted benzoylpivaloylmethanes and their copper(II) chelates are described, i H n.m.r., u.v. and i.r. spectra of free ligands indicate a very high enol content. Molecular weight determinations showed that the bulky t-butyl and phenyl groups do not prevent association of chelates in chloroform solutions. All the chelates obey the Curie-Weiss law with the Weiss constant close to zero; magnetic moments lie within the 1.87-2.02 B.M. rangeover the 77 300Krange. l.r. and Raman s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The ligand benzoylpivaloylmethane (Hbpm) was first synthesized by Vorländer and Kalkow in 1898 . From UV, IR, and 1 H NMR spectroscopy it was concluded that the diketone exists mainly as PhCOCH(OH)CMe 3 (Ph, phenyl; Me, methyl). Up to now, only benzoylpivaloylmethanide complexes with alkaline earth and transition metals have been described in the literature …”
Section: Resultsmentioning
confidence: 99%
“…The ligand benzoylpivaloylmethane (Hbpm) was first synthesized by Vorländer and Kalkow in 1898 . From UV, IR, and 1 H NMR spectroscopy it was concluded that the diketone exists mainly as PhCOCH(OH)CMe 3 (Ph, phenyl; Me, methyl). Up to now, only benzoylpivaloylmethanide complexes with alkaline earth and transition metals have been described in the literature …”
Section: Resultsmentioning
confidence: 99%